Identification of a Novel Stem Cell Subtype for Clear Cell Renal Cell Carcinoma Based on Stem Cell Gene Profiling - Wang, Hongzhi; Xu, Hanjiang; Cheng, Quan; Liang, Chaozhao (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma is the most common subtype of renal cancer and characterized by high rates of metastasis. Cancer stem cell is a vital cause of renal cancer metastasis and recurrence. However, little is known regarding the change and roles of stem cells during the development of renal cancer. To clarify this problem, we developed a novel stem cell clustering strategy. Based on TCGA and ICGC genomic datasets, we used 19 stem cell gene sets to classify each dataset. Machine learning method was used to perform the classification. We classified ccRCC into three subtypes, stem cell activated (SC-A), stem cell dormancy (SC-D) and stem cell excluded (SC-E), based on the expression of stem cell related genes. Compared with other subtypes, C2(SC-A) had the has the highest degree of cancer stem cell concentration, highest level of immune cell infiltration, distinct mutation landscape and worst prognosis. Moreover, drug sensitivity analysis reveals that C2(SC-A) subgroup has highest sensitivity to immunotherapy CTLA-4 blockade and VEGFR inhibitor Sunitinib. The identification of ccRCC subtypes based on cancer stem cell gene sets demonstrates the heterogenicity of ccRCC and provided a new strategy for treatment of ccRCC.